2022
DOI: 10.1002/jbt.23255
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl functionalized 5,6‐dimethylbenzimidazolium salts: Synthesis and biological activities

Abstract: A series of vinyl functionalized 5,6-dimethylbenzimidazolium salts are synthesized.All compounds were fully characterized by elemental analyses, MS, 1 H-NMR, 13 C-NMR, and IR spectroscopy techniques. Enzyme inhibition is a very active area of research in drug design and development. In this study, the synthesized novel benzimidazolium salts were evaluated toward the human erythrocyte carbonic anhydrase I (hCA I), and II (hCA II) isoenzymes, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 92 publications
2
2
0
Order By: Relevance
“…The enzyme BChE catalyzes the breakdown of neurotransmitters into butyrate and choline to act on butyrylcholine and stop its effects in the synaptic cleft. [85][86][87] In the current study, a significant decrease was also observed between the control and HL+bromelain groups in the liver (*p < 0.05; Figure 3). Moreover, a similar situation was observed between the HL-control and HL+bromelain groups in liver (*p < 0.05; Figure 3).…”
Section: Resultssupporting
confidence: 68%
“…The enzyme BChE catalyzes the breakdown of neurotransmitters into butyrate and choline to act on butyrylcholine and stop its effects in the synaptic cleft. [85][86][87] In the current study, a significant decrease was also observed between the control and HL+bromelain groups in the liver (*p < 0.05; Figure 3). Moreover, a similar situation was observed between the HL-control and HL+bromelain groups in liver (*p < 0.05; Figure 3).…”
Section: Resultssupporting
confidence: 68%
“…In the study on vinyl functionalized 5,6‐dimethylbenzimidazolium salts, the Ki value for hCA I was found to be 484.8‐1389.7 nM, the Ki value for hCA II was 298.9–926.1 nM, and the Ki value for AChE was 27.1–77.6 nM. In our study, trifluoromethoxybenzyl groups exhibited better inhibition effects on hCAI and hCA II enzymes compared to this study, and showed parallelism in the inhibition of AChE enzyme [75] …”
Section: Resultssupporting
confidence: 49%
“…They play a role in regulating the acidity of gastric juice and in the secretion of mucus and bicarbonate from epithelial cells on tissue surfaces in the gastrointestinal tract. In addition, the hCA II isoenzyme is effective in adjusting the intracellular pH and Ca 2+ level to prevent bone resorption [ 82 ]. Most hCA I is found in erythrocytes.…”
Section: Discussionmentioning
confidence: 99%